Further Data Supporting that the Paclitaxel-Associated Acute Pain Syndrome is Associated with the Development of Peripheral Neuropathy: NCCTG Trial N08C1() - Reeves, Brandi N. (2012)
BACKGROUND: Paclitaxel causes an acute pain syndrome (P-APS), occurring within days after each dose and usually abating within days. Paclitaxel also causes a more classic peripheral neuropathy, which steadily increases in severity with increasing paclitaxel total doses. Little detail is available regarding the natural history of these two syndromes, or any relationship between them, although a recent publication does provide natural history data about weekly paclitaxel, supporting an association between the severity of P-APS and eventual peripheral neuropathy symptoms. METHODS: Patients entering this study were about to receive paclitaxel and carboplatin every 3 weeks. Daily questionnaires were completed for the first week after every chemotherapy dose and EORTC QLQ-CIPN 20 instruments were completed weekly. RESULTS: The P-APS severity peaked on day 4 after the initial chemotherapy dose, with 12%, 29%, 23%, and 36% of patients having maximal pain scores of 0, 1–4, 5–6, or 7–10 during the first week after the first dose of therapy, respectively. Patients with P-APS scores of 0–4 with the first dose of chemotherapy had less eventual sensory neuropathy than did patients with P-APS scores of 5–10 (p=0.001). With regard to the more peripheral neuropathy, sensory neuropathy was more problematic than was either motor or autonomic neuropathy. Numbness and tingling were more common components of the sensory neuropathy, than was pain. CONCLUSIONS: Patients with worse P-APS severities appear to have more eventual chemotherapy induced peripheral neuropathy. This provides support for the concept that the P-APS is a form of nerve pathology.